2011
DOI: 10.5582/ddt.2011.v5.4.195
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effect of <i>Withania somnifera</i> on inflammation in a non-autoimmune prone murine model of lupus

Abstract: The immunosuppressive properties of an aqueous suspension of Withania somnifera (WS) root powder were investigated in a pristane induced female Balb/c model of a systemic lupus erythematosus (SLE) like disease. The course of disease is initiated by peritoneal inflammation caused by pristane which results in development of SLE like symptoms, i.e. autoantibody production, proteinuria, and nephritis within a period of five to six months. The model of SLE was established by injecting 0.5 mL of pristane intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
0
8
0
2
Order By: Relevance
“…for review) contributing to mitochondrial function and inducing cell death. In this regard, it has widely reported that Wse show a potent inhibitory effect on inflammatory markers such as ROS in a mouse model of lupus4647. Interestingly Wse reduced rotenone-induced oxidative impairment and mitochondrial respiratory chain enzymes and such impairments were responsible for reduced locomotor deficits and lethality in a Drosophila melanogaster model of Parkinson induced by rotenone, a naturally occurring common pesticide which specifically inhibits mitochondrial complex-I activity48.…”
Section: Discussionmentioning
confidence: 99%
“…for review) contributing to mitochondrial function and inducing cell death. In this regard, it has widely reported that Wse show a potent inhibitory effect on inflammatory markers such as ROS in a mouse model of lupus4647. Interestingly Wse reduced rotenone-induced oxidative impairment and mitochondrial respiratory chain enzymes and such impairments were responsible for reduced locomotor deficits and lethality in a Drosophila melanogaster model of Parkinson induced by rotenone, a naturally occurring common pesticide which specifically inhibits mitochondrial complex-I activity48.…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic effects of WS extract were characterized by orally administering WS for one month prior and six months following pristane injections. WS treatment resulted in significant reductions in ROS formation within intraperitoneal macrophages, as well as reductions in inflammatory cytokines (IL-6 and TNF-α), and decreased inflammation within the kidneys, liver, and lung, however, no reduction in the humoral response autoantibodies or immune complex deposition [180,181].…”
Section: Therapeutic Benefits Of Withanolides For Sle and Ibd In Vivomentioning
confidence: 97%
“…Reactive oxygen species (ROS) play a major pathogenic role in a wide range of types of human [1] and experimental [2], [3] glomerulonephritis, including IgA nephropathy (IgAN) [4][7]. Importantly, in both patients [4], [5], [8] and animal models [7], [9], [10], ROS have been shown to be involved in the progressive stage of IgAN, the most common type of primary glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%